2014
DOI: 10.1007/s00264-014-2468-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different cement application techniques for tibial component fixation in TKA

Abstract: Adequate surface preparation using pulsed lavage and copious drying of the tibial surface appears to be of overruling importance, thus limiting the effect of any particular technique applied to improve implant fixation. This study emphasises the fundamental importance of surface preparation and pulsed lavage in TKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 41 publications
(60 reference statements)
0
27
0
1
Order By: Relevance
“…Possible influencial factors may be reduced to shortcomings in surgical technique or implant-related issues. Cementation technique still remains a matter of discussion in primary TKA [3, 18, 19, 24]. Kopinski et al found a connection between the use of high-viscosity cement and early tibial debonding [11].…”
Section: Discussionmentioning
confidence: 99%
“…Possible influencial factors may be reduced to shortcomings in surgical technique or implant-related issues. Cementation technique still remains a matter of discussion in primary TKA [3, 18, 19, 24]. Kopinski et al found a connection between the use of high-viscosity cement and early tibial debonding [11].…”
Section: Discussionmentioning
confidence: 99%
“…31 Final preparation of the bone-cement interface is best performed using pulsed lavage. In separate studies, Schlegel et al 32,33 confirmed the importance of bone preparation and pulsed lavage in enhancing fixation strength and recommended that it is a mandatory step in surface preparation along with copious drying of the tibial surface when cementing tibial components in TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to obtain an optimal cement bone interface shear strength through interdigitation, a 3–5 mm cement penetration depth has been advised. Techniques using a spatula, finger pressing, and a cement gun have been suggested to improve penetration of cement into bone3,16,17). In contrast, the ideal thickness of cement mantle that bonds the prosthesis to the bone at the interface has been considered ≤1 mm12).…”
Section: Discussionmentioning
confidence: 99%